2015
DOI: 10.1111/sum.12209
|View full text |Cite
|
Sign up to set email alerts
|

A review of ammonia emission measured using wind tunnels compared with micrometeorological techniques

Abstract: Ammonia (NH3) emission from livestock manure constitutes a loss of crop‐available nitrogen (N) and poses a threat to the environment. Therefore, low NH3 emission slurry application technologies have been developed, the reduction efficiency of which has typically been estimated through measurements using wind tunnels or integrated horizontal flux (IHF) micrometeorological techniques. A recovery of 100% of released NH3 can be obtained if wind tunnels are designed to avoid pulses of wind into the tunnel through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…1a), which was determined by field sonic anemometers, placed 0.25 m above the soil surface, in 2013 and 2014 to be representative of average near-surface wind speeds at the field site (data not shown). Adjusting wind speed to represent ambient conditions (at 0.25 m) can provide ammonia volatilization values in statistical agreement with IHF results (Sommer and Misselbrook 2016). Wind speed can directly affect ammonia volatilization rates within wind tunnels.…”
Section: Wind Tunnel Designsupporting
confidence: 72%
See 2 more Smart Citations
“…1a), which was determined by field sonic anemometers, placed 0.25 m above the soil surface, in 2013 and 2014 to be representative of average near-surface wind speeds at the field site (data not shown). Adjusting wind speed to represent ambient conditions (at 0.25 m) can provide ammonia volatilization values in statistical agreement with IHF results (Sommer and Misselbrook 2016). Wind speed can directly affect ammonia volatilization rates within wind tunnels.…”
Section: Wind Tunnel Designsupporting
confidence: 72%
“…Sommer et al (1991) showed a positive increase in losses, from cattle slurry, up to 2.5 m s −1 , whereas increases in wind speed beyond 2.5-4 m s −1 did not influence loss. Sommer and Misselbrook (2016) suggested having relatively high wind speeds will increase the likelihood of agreement with the IHF method, as the laminar boundary layer resistance will no longer be the controlling factor for ammonia volatilization loss.…”
Section: Wind Tunnel Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the current study suggests that ammonia losses from urea usage in a temperate maritime climate are much lower than the values obtained from wind tunnels. This is perhaps not so surprising when one considers that Ryden and Lockyer () reported that wind tunnels can overestimate ammonia losses by a factor of 2.4–6 during rainfall and that Sommer & Misselbrook () report that wind tunnels which are adjusted to match ambient airflow could give results similar to integrated horizontal flux for periods without rainfall. In the parallel study of Forrestal et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the last decades, most of the tests performed on NH 3 volatilization from manure and mineral fertilizers at field-scale or in in agronomic plots, were measured with the Integrated Horizontal Flux (IHF) technique, the ZINST method, the inverse dispersion modelling (IDM) coupled with concentration measurements, or with wind tunnels [13][14][15]. Agronomic plots of 20 m in radius treated with manure are the most common design in the tests of low emitting spreading technologies [14], and the IHF is often considered as a reference method to assess NH 3 emissions [12,16]. In the typical tests, IHF is used to measure emission from relatively large plots (radius of 20 m) which demands a large distance between coexisting plots to avoid advection interferences; consequently, few or no replications at plot-level are carried out.…”
Section: Introductionmentioning
confidence: 99%